PENGGUNAAN MODEL DIRECT INSTRUCTION DALAM MENINGKATKAN KREATIVITAS MEMBUAT BINGKAI GAMBAR MELALUI PADA PEMBELAJARAN SENI RUPA KELAS V SDN 11 LIMBOTO KABUPATEN GORONTALO - Hermin Susanti; Fandi H. Binggo (Jurnal Ilmu Pendidikan UMGo, 2025)
The purpose of this study was to increase creativity in making picture frames through the direct instruction model in the learning of fine arts for class V at SDN 11 Limboto, Gorontalo Regency. The type of research used in this research is classroom action research with the research subject of 25 fourth grade students at SDN 11 Limboto. This study uses techniques, namely interviews, observations, tests, and documentation. Data analysis techniques are data on educator activities, student activity data and students' speaking skills. The research was carried out in two cycles.The results of the research in the initial observation there were 8 students or 32% later, in the first cycle there was an increase with students whose creativity in making picture frames had reached the minimum completeness criteria of 75. In the first cycle that was completed there were 17 people with a percentage of 68% while in the first cycle there were 17 people with a percentage of 68%. II, there are 23 students whose speaking ability has reached completeness with a percentage of 92%. Thus, it can be concluded that the Direct Instruction Model Can Increase Creativity in Making Picture Frames in Visual Arts Learning Class V SDN 11 Limboto.